Effect of agriculture on soil properties associated with soil health and fertility in the Argentinean Pampas - Sainz Rozas, Hernan Rene; Eyherabide, Mercedes; Larrea, Gaston Emiliano; Angelini, Hernán Pablo; Reussi Calvo, Nahuel Ignacio; Wyngaard, Nicolás (Food and Agriculture Organization of the United Nations (FAO), 2023)
During the last four decades, the Argentinean Pampas Region (APR) (lat: 33o 23’S to 38o 47’S, long: 57o 36’W to 65o 10’W) has been subjected to a land use change process known as “agriculturization”, which is the conversion of native grasslands into croplands. This process can result in the depletion of soil organic matter (SOM) and nutrients availability. However, the extent of this degradation process remains unknown (Wyngaard, 2022). The aim of this study was to determine the current levels of SOM, pH, extractable P (Bray-P), and other nutrients (Ca, Mg, K, Zn, Mn, Cu and Fe) in pristine and cultivated soils.